2020
DOI: 10.1007/jhep06(2020)152
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussianities and tensor-to-scalar ratio in non-local R2-like inflation

Abstract: In this paper we will study R 2-like inflation in a non-local modification of gravity which contains quadratic in Ricci scalar and Weyl tensor terms with analytic infinite derivative form-factors in the action. It is known that the inflationary solution of the local R + R 2 gravity remains a particular exact solution in this model. It was shown earlier that the power spectrum of scalar perturbations generated during inflation in the non-local setup remains the same as in the local R + R 2 inflation, whereas th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 91 publications
4
67
0
Order By: Relevance
“…Inflation has been considered in nonlocal theories of gravity as well [40], where the classical action contains infinitely many free parameters. The cosmological perturbations in those scenarios have been studied in [41,42].…”
Section: Jhep07(2020)211mentioning
confidence: 99%
“…Inflation has been considered in nonlocal theories of gravity as well [40], where the classical action contains infinitely many free parameters. The cosmological perturbations in those scenarios have been studied in [41,42].…”
Section: Jhep07(2020)211mentioning
confidence: 99%
“…In facts, it has been shown that the model has a satisfactory Starobinsky-like inflation [32,33]. The spectrum of scalar perturbations generated during inflation is the same as in the local R 2 inflation [82], while tensor perturbations are affected by the non-locality [34][35][36]; indeed, NLQG is predictive.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that the Minkowski spacetime is stable under any Strongly Asymptotically Flat (SAF) initial data set satisfying a Global Smallness Assumption (GSA) [29], as in general relativity. Moreover, the model has a satisfactory Starobinsky-like inflation [52,53], and the spectrum of JHEP09(2020)056 scalar perturbations generated during inflation is the same as in the local Starobinsky R 2 inflation [54], while the spectrum of tensor perturbations is affected by the nonlocality, see [55][56][57] for the details. Indeed, nonlocal gravity can be falsified by future measurements of tensor perturbations.…”
Section: Introductionmentioning
confidence: 99%